Metrics 101 : what to measure on your website - Power, Sean (O'Reilly Media, 2010)
"This video helps you build a complete web monitoring strategy. It covers the many different metrics you can collect, from latency and uptime to usability and navigation--and show you how to tie them to the goals of your web business. Presented by the co-author of O'Reilly's Complete Web Monitoring, this video looks at every part of your online measurement strategy, with a particular focus on what web operators need to know"--Resource description page.